2011
DOI: 10.1007/s10571-011-9735-9
|View full text |Cite
|
Sign up to set email alerts
|

A Much Convenient and Economical Method to Harvest a Great Number of Microglia

Abstract: Microglia, implicating in such neuro-pathologies as brain inflammation, neurodegeneration, glioma, and neurogenesis, play an important role in central nervous system. Advanced research on microglia is crucial in exploring the neuro-pathology and neuro-physiology of these diseases, so how to culture large numbers of microglia in vitro becomes the base of a research. The wildly used method, at present, obtaining microglia from murine cannot fulfill the requirement of research, costing too much time and needing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…23 There have been several protocols developed over the past decade to isolate primary microglia. 8,10,11,14,15,18,[31][32][33] Protocols can be found to isolate microglia from neonatal or adult mice and utilize a variety of methods, including the use of proprietary kits, magnetic bead separation, and Percoll gradients. None of the protocols we found in the literature determine the purity of their microglial population using the latest microglial-specific markers, which can distinguish them from other types of macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 There have been several protocols developed over the past decade to isolate primary microglia. 8,10,11,14,15,18,[31][32][33] Protocols can be found to isolate microglia from neonatal or adult mice and utilize a variety of methods, including the use of proprietary kits, magnetic bead separation, and Percoll gradients. None of the protocols we found in the literature determine the purity of their microglial population using the latest microglial-specific markers, which can distinguish them from other types of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently several published methods describing microglial isolation; however, these protocols are often cumbersome and/or fail to confirm microglial purity using microglialspecific markers. [8][9][10][11] For example, Magnetic-Activated Cell Sorting (MACS) is widely used to isolate immune cells, including microglia. 12 However, in our hands, Miltenyi's popular MACS kits often took an entire day, often up to 12 h, and resulted in very few cells per brain, even after multiple rounds of optimization.…”
Section: Impact Statementmentioning
confidence: 99%
“…Generally, the induced oxidative stress has been described as a trigger of neuronal cell death, endothelial proliferation, glia activation, inflammation and in some cases proliferation in specific brain regions. 15 , 16 , 21 – 24 In addition, our previous findings of glia activation, neuronal degeneration and proliferation induced by differential oxidative stress has revealed that regional differences exists in stress response elicited in the brain; specifically across the plastic and non-plastic brain regions. 25 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to shorter agitation times, e.g., 45 min or 3 h (Flode and Combs, 2007;Gingras et al, 2007), more vigorous methods such as 180 rpm for 15 h (Giulian and Baker, 1986) or 150 rpm for 16 h (Hassan et al, 1991) were also used. Other authors used gentle agitation, e.g., shaking the flasks by hand and gently blowing with a pipette (Qin et al, 2012) or gently banging on the side and tapping the flasks at a speed of 45 rpm for about 9-12 min (Ni and Aschner, 2010). Typical protocols reported enzymatic digestion using differential adhesion steps with the shaking off of non-adherent cells after 2 or 24 h (Yip et al, 2009) or just 10 min (Gingras et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Typical protocols reported enzymatic digestion using differential adhesion steps with the shaking off of non-adherent cells after 2 or 24 h (Yip et al, 2009) or just 10 min (Gingras et al, 2007). While some researchers used a microglia enrichment step only once (Saura et al, 2003;Rustenhoven et al, 2016), others isolated microglia repeatedly from the same primary culture: 3 times after 7 days (Flode and Combs, 2007), 3 times after 8-10 days with passage (Qin et al, 2012), 2 times after 1 month (Gingras et al, 2007) and twice a week from the supernatant without shaking up to 32 days (Moussaud and Draheim, 2010). The purity of these microglia-enriched cultures was typically high and was accompanied by a low yield.…”
Section: Discussionmentioning
confidence: 99%